2003
DOI: 10.1242/jcs.00622
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of F-actin-dependent processes by the Abl family of tyrosine kinases

Abstract: The F-actin cytoskeleton is a fundamental component of all eukaryotic cells. It provides force and stability and plays an integral role in a diverse array of cellular processes. The spatiotemporal regulation of F-actin dynamics is essential for proper biological output. The basic molecular machinery underlying the assembly and disassembly of filamentous actin is conserved in all eukaryotic cells. Additionally, protein tyrosine kinases, found only in multicellular eukaryotes, provide links between extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
215
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(224 citation statements)
references
References 141 publications
6
215
1
2
Order By: Relevance
“…Among the molecular modulators of cytoskeletal organization are the Abl family tyrosine kinases c-Abl and Arg (Abl1 and Abl2) that regulate actin dynamics by phosphorylating cytoskeletal proteins and through direct F-actin binding (Woodring et al, 2003;Hernandez et al, 2004). In addition to a catalytic domain, they possess SH3-, SH2-and actin-binding domains (Pendergast, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among the molecular modulators of cytoskeletal organization are the Abl family tyrosine kinases c-Abl and Arg (Abl1 and Abl2) that regulate actin dynamics by phosphorylating cytoskeletal proteins and through direct F-actin binding (Woodring et al, 2003;Hernandez et al, 2004). In addition to a catalytic domain, they possess SH3-, SH2-and actin-binding domains (Pendergast, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that c-Abl contains intramolecular interactions that provide autoinhibitory mechanisms (Pendergast, 2002;Pluk et al, 2002;Hantschel et al, 2003). Studies have also found that c-Abl kinase activity is regulated by intermolecular interactions with negative regulators, which include Bcr (Liu et al, 1996;Ling et al, 2003), PAG (Wen and Van Etten, 1997) and F-actin (Woodring et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitously expressed Abl tyrosine kinase is a transducer of a variety of cell extrinsic and intrinsic signals including those from growth factors, cell adhesion, oxidative stress and DNA damage [10,11]. The Abl protein contains three nuclear localization signals (NLS), Fig.…”
Section: Dna Damage and Tnf Induced Apoptosis Involves Ablmentioning
confidence: 99%
“…The N-terminal region of Abl resembles the Src-family of tyrosine kinases and adopts an auto-inhibited conformation assembled through intramolecular interactions among its SH3-SH2-kinase domains [13,14]. The C-terminal region of Abl contains subcellular location cues, including NLS, NES, binding sites for G-actin, F-actin and binding site for DNA [10,11]. We have shown that F-actin, but not G-actin, is an allosteric inhibitor of Abl tyrosine kinase [15].…”
Section: Dna Damage and Tnf Induced Apoptosis Involves Ablmentioning
confidence: 99%
See 1 more Smart Citation